EPISTEMOLOGI IDEOLOGI KEAMANAN PANGAN - Yusuf Adiwibowo (Yuridika, 2016)
Food safety issues have a significant impact on the socio-economic life of this world, which is characterized by the global spread of the virus hazards, microbial pathogens and pesticide residues that cause health problems and even death. In order to protect the state from the threat of viral, microbial pathogens and pesticide residues, the developed states apply the standards for the trade barriers so that the hazardous contaminated products can be prevented to enter to their states. Islamic Epistemology describes the food security in Qur'an as Surat Al-Baqoroh paragraph 2: 168 "eat the halal and good". Halal foods is the right of Allah to justified. Good food is a food that provides peace and containts no danger. This is in line with the ideology of Pancasila and the Constitution as the basic philosophy of the establishment of laws and regulations of Indonesia. Food safety has been sought by both international organizations and countries in the world. The effort is done with a solid instrument and packaged in an international agreement which is then accessed and implemented in national legislation.